Frontiers in diagnostic and therapeutic approaches in diabetic sensorimotor neuropathy (DSPN) - Sharma, Sanjeev; Rayman, Gerry (Frontiers in Endocrinology, 2023)
Diabetes sensory polyneuropathy (DSPN) is a significant complication of diabetes affecting upto 50% of patients in their lifetime and approximately 20% of patients suffer from painful diabetes neuropathic pain. DSPN – both painless and painful - leads to considerable morbidity including reduction of quality of life, increased lower limb amputations and is associated with worsening mortality. Significant progress has been made in the understanding of pathogenesis of DSPN and the last decade has seen newer techniques aimed at its earlier diagnosis. The management of painful DSPN remains a challenge despite advances made in the unravelling the pathogenesis of pain and its transmission. This article discusses the heterogenous clinical presentation of DSPN and the need to exclude key differential diagnoses. Furthermore, it reviews in detail the current diagnostic techniques involving both large and small neural fibres, their limitations and advantages and current place in the diagnosis of DSPN. Finally, the management of DSPN including newer pharmacotherapies are also discussed.